The Long-Term Labor Market Effects of Parental Unemployment - Bernhard Schmidpeter (ZBW - Leibniz Information Centre for Economics, 2020)
I investigate the impact of parental unemployment on children's educational attainment and long-run labor market outcomes in Austria. I find that parental unemployment shortly before an important educational decision by parents for their children lowers a child's probability of holding a university degree by more than 5 percentage points. I do not find that income is affected at the beginning of a child's labor market career along the distribution but find a gradual deterioration later on. A substantial share of these long-term losses can be explained by the lower parental investment decision. My results emphasize the intergenerational and long-lasting consequences of parental unemployment.
Keywords: C21; I23; J13; J31; J64; 330; Parental Unemployment; Intergenerational Effects; Long-Term Effects; Unemployment; Wage Loss; Decomposition